The Use of Informal Affixation in Social Media Threads as Teaching Material for Indonesian Language in High School - Rohadatul Aisy Agung Fauziah; Agus Budi Wahyudi (Journal La Sociale, 2023)
This research focuses on informal forms of affixation on social media threads. The aims of this research are (1) to describe forms of informal affixation, (2) to describe the implementation of research results on informal affixation on social media threads as an alternative teaching material in high school. This type of research is qualitative descriptive research which aims to describe forms of informal affixation. The data in the research are all words that contain informal affixations on Threads social media. Data collection techniques use documentation, reading, listening and note-taking techniques. The results of this research show that there are two types of informal affixations on the objects studied, namely first, informal verb-forming affixations in the form of the suffix -an, suffix -in, prefix ke-, combination di-in. Second, the informal affixation that forms adjectives is in the form of the affix -an and the affix -an. Third, implementation of research data in news text teaching materials in high school with Learning Outcomes (CP) where students are able to write ideas and thoughts in news texts with clear and neat writing paying attention to appropriate punctuation.